Comparative Analysis of Actuation Response in Silicone and Polyurethane Rubber Manipulators - Santos, Marcella Geovanna Silva Dos; Mendes, João Vitor Silva; Dias, Paula Do Patrocínio; Vieira, Jamile Almeida; Pisanu, Luciano; Silva, Lucas Cruz Da (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2023: Anais do XV Simpósio Brasileiro de Robótica e XX Simpósio Latino Americano de Robótica, 2023)
Soft materials distribute the loads over a larger area, allowing greater distribution of stresses and a better absorption of the dynamic loads and shocks. Polymeric materials, such as silicone rubber and polyurethane (PU), are naturally flexible and undergo reversible elastic deformation. They present different characteristics due to variations in their chemical compositions and manufacturing processes. In this study, the movement of manipulators made of silicone rubber and polyurethane with different hardness were compared to understand their performance and motor behavior. A camera with fiducial markers was used to capture the motion of the manipulators and infer motor data. The curvature angle was calculated using the position variation of the markers. Motor data, including current and torque, were collected using a data acquisition system. The results showed that the silicone manipulator had lower mechanical strength and was susceptible to tearing and breaking. The PU with a hardness of 45 A presented the lowest curvature capacity, requiring the highest torque, and faced challenges with tendon fixation. The PU with a hardness of 20 achieved the greatest curvature, requiring the lowest torque, without damage to the manipulator’s body. It showed excellent flexibility and mechanical resistance. These findings highlight the importance of carefully selecting materials when designing flexible manipulators.